2015
DOI: 10.1103/physrevd.92.023521
|View full text |Cite
|
Sign up to set email alerts
|

Constraints on cosmic strings from ultracompact minihalos

Abstract: Cosmic strings are expected to form loops. These can act as seeds for accretion of dark matter, leading to the formation of ultracompact minihalos (UCMHs). We perform a detailed study of the accretion of dark matter onto cosmic string loops and compute the resulting mass distribution of UCMHs. We then apply observational limits on the present-day abundance of UCMHs to derive corresponding limits on the cosmic string tension $G\mu$. The bounds are strongly dependent upon the assumed distribution of loop velocit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 63 publications
0
20
0
Order By: Relevance
“…It is in any case interesting to ask how the dark matter substructure would change if the initial small scale perturbations were larger than expected. Other papers which constrain the power spectrum on small scales include [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35]. In particular, we note that CMB spectral distortion constraints provide an upper bound on the primordial power spectrum on about the same scales as UCMHs, which are about an order of magnitude weaker than the currently claimed constraints but independent of the DM model [20].…”
Section: Introductionmentioning
confidence: 65%
“…It is in any case interesting to ask how the dark matter substructure would change if the initial small scale perturbations were larger than expected. Other papers which constrain the power spectrum on small scales include [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35]. In particular, we note that CMB spectral distortion constraints provide an upper bound on the primordial power spectrum on about the same scales as UCMHs, which are about an order of magnitude weaker than the currently claimed constraints but independent of the DM model [20].…”
Section: Introductionmentioning
confidence: 65%
“…Complementary but weaker constraints can also be obtained from CMB spectral distortions [23,24]. These limits constrain the processes that could have formed UCMH-seeding overdensities in the early Universe [10,11,16,21,[25][26][27][28].…”
mentioning
confidence: 97%
“…Scan 1 adds PBH constraints, employing a step-function likelihood from the implementation of the limits of Ref. [15] in Dark-SUSY [28], following Ref. [10].…”
mentioning
confidence: 99%
“…In fact, it has been shown that the power spectrum of a string-induced density perturbation component is expected to dominate over a primordial inflationary component on small enough scales [245]. In this context, cosmic strings have been suggested to have significant impact on the formation of ultracompact minihalos [39], globular clusters [40], super-massive black holes [41] and to provide a significant contribution to the reionization history of the Universe [42]. The dynamics of cosmic defects, in particular of domain walls, has also been associated to possible variations of the fundamental couplings of nature (see, e.g., [38]).…”
Section: Observational Signatures Of Topological Defectsmentioning
confidence: 99%
“…For instance, they may be associated to spatial variations of the fundamental couplings of nature (see, e.g., [38]). On the other hand, cosmic strings may contribute significantly to small-scale cosmological perturbations and have consequently been suggested to have significant impact on the formation of ultracompact minihalos [39], globular clusters [40], super-massive black holes [41] and to provide a significant contribution to the reionization history of the Universe [42]. Both cosmic strings and domain walls may be responsible for significant contributions to two of the most significant observational probes: the temperature and polarization anisotropies of the cosmic microwave background and the stochastic gravitational wave background.…”
Section: Introductionmentioning
confidence: 99%